Details behind the dots: How different intensive care units used common and contrasting methods to prevent ventilator associated pneumonia. Issue 1 (12th March 2015) - Daniel, Malcolm; Booth, Malcolm; Ellis, Kirsteen; Maher, Shaun; Longmate, Andrew
Abstract: Care bundles promote delivery of effective care and improve patient outcomes. The understanding of how to improve delivery of care bundles is incomplete. The Scottish Patient Safety Programme is a national collaborative with the aim of improving the delivery of care to patients in acute hospitals in Scotland. Critical care is one of five workstreams in the programme. A programme goal is to reduce incidence of ventilator-associated pneumonia (VAP) to zero or 300 calendar days between events through use of a VAP Prevention bundle. We studied two ICUs participating in this programme. Each ICU had established infection surveillance system prior to the programme starting. Both units had an appreciable incidence of VAP. Initial VAP prevention bundle adherence was low in each ICU (35% and 41%). Comparing time periods before and after 80% bundle VAP prevention bundle adherence was achieved showed a similar reduction in VAP incidence (from 6.9 to 1.0, and from 7.8 to 1.4/1000 ventilation days). When compared each ICU used common and contrasting approaches to accomplish this improvement. We describe the five improvement knowledge systems used to improve bundle adherence to bundle elements in each hospital. The insights gained from these front-line clinical teams can be used as a template for improvement efforts in a variety of other healthcare settings.